2021
DOI: 10.33687/ijae.009.03.3789
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory factor analysis of the perceived constraints affecting rice farmers of kano river irrigation (KRIP) kano state, Nigeria

Abstract: To empirically factor out the perceived constraints affecting rice production in the Kano River Irrigation Project Kano State, Nigeria, the current study used cross-sectional data collected through a semi-structured questionnaire complemented by an interview schedule from 217 rice farmers selected via a multi-stage sampling technique in 2020. High input cost, inadequate training, unreliable water supply, waterlogging, and insufficient credit were identified as significant risk factors affecting rice production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The project area is situated in a vast area of over 25 km south of Kano city and is one of the functional irrigation schemes in the country. It is designed to provide irrigation facilities to about 22,000 hectares of land utilizing water release from the Tiga dam through the Ruwan Kanya reservoir (Wudil et al, 2021). The scheme operates in three local government areas: Kura, Garum Mallam, and Bunkure.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The project area is situated in a vast area of over 25 km south of Kano city and is one of the functional irrigation schemes in the country. It is designed to provide irrigation facilities to about 22,000 hectares of land utilizing water release from the Tiga dam through the Ruwan Kanya reservoir (Wudil et al, 2021). The scheme operates in three local government areas: Kura, Garum Mallam, and Bunkure.…”
Section: Study Areamentioning
confidence: 99%
“…The project aimed at increasing food production and productivity, improve the beneficiaries' income, provide employment opportunities and reduce food insecurity (Yusuf et al, 2020). The study purposively used rice farmers for the study because rice is cultivated in more than 70% of the cropped area (Wudil et al, 2021). The crop is also one of the most consumed staples in Nigeria (Uduma et al, 2016;Fawole and Aderinoye-Abdulwahab, 2021) while available statistics showed that Nigerians consume more than seven million metric tons of rice in 2020 (Ihedioha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%